2017
DOI: 10.1186/s12284-017-0162-5
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of the Rice Gene LRR1 Compromises Rice Xa21 Transcript Accumulation and XA21-Mediated Immunity

Abstract: BackgroundThe rice immune receptor XA21 confers resistance to Xanthomonas oryzae pv. oryzae (Xoo), the causal agent of bacterial leaf blight. We previously demonstrated that an auxilin-like protein, XA21 BINDING PROTEIN 21 (XB21), positively regulates resistance to Xoo.ResultsTo further investigate the function of XB21, we performed a yeast two-hybrid screen. We identified 22 unique XB21 interacting proteins, including LEUCINE-RICH REPEAT PROTEIN 1 (LRR1), which we selected for further analysis. Silencing of L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 32 publications
(66 reference statements)
0
8
0
Order By: Relevance
“…Similarly, silencing of an LRR1 gene was found to compromise resistance to the bacterial pathogen Xanthomonas oryzae pv. oryzae in rice ( Oryza sativa L.) (Caddell et al., 2017). In GWAS studies of sorghum mini core collection and SAP lines, regarding anthracnose and head smut, leucine rich repeat containing proteins were listed as top candidate genes associated with response to anthracnose (Ahn et al., 2019; Cuevas et al., 2018a; Prom et al., 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, silencing of an LRR1 gene was found to compromise resistance to the bacterial pathogen Xanthomonas oryzae pv. oryzae in rice ( Oryza sativa L.) (Caddell et al., 2017). In GWAS studies of sorghum mini core collection and SAP lines, regarding anthracnose and head smut, leucine rich repeat containing proteins were listed as top candidate genes associated with response to anthracnose (Ahn et al., 2019; Cuevas et al., 2018a; Prom et al., 2019).…”
Section: Resultsmentioning
confidence: 99%
“…This gene encodes an immune receptor kinase whose functions result in subsequent activation of an intracellular defence response. Additionally, a previous study found that silencing OsXA21 led to rice susceptibility to Xoo infection [82]. Recently, Ye et al [80] reported that many RLKs are involved in responses to abiotic stresses, including the salt-stress response in plants.…”
Section: Discussionmentioning
confidence: 99%
“…Of the other six protein-types several had mutations on leucine rich repeats (LRR); LRR4, LRR9, LRR10 and LRR22, and on the NLS. The LRR repeats are previously reported to be associated with disease resistance conveyed via Xa genes (Caddell et al, 2017), and hence, a mutation in these repeats could alter the function of the gene. Therefore, further studies to verify the identified protein-types through phenotypic assays are recommended.…”
Section: Thirteen Confirmed Xa21 Haplotypes and Nine Protein-typesmentioning
confidence: 99%